Internet dating as a project - Žakelj, Tjaša (Družboslovne razprave, 2015)
Based on qualitative empirical data from two studies on Internet dating in Slovenia, this paper discusses the social contexts of the Internet dating of heterosexual men and women and homosexual men. Special attention is given to different aspects of the commodification and rationalisation of dating in the process of forming potential (romantic) partnerships. First, we discuss our respondents' reasons for using the Internet to get in touch with potential (romantic) partners. Second, we focus on the demands and strategies of targeted marketing in personal profile writing and, finally, on the process of selecting potential partners. Our study shows that the primary understanding of Internet dating among people who engage in it is its economic nature. Together with targeted marketing and the predetermined criteria for choosing interesting others, Internet dating can thus be understood as a market that encourages rationalisation and commodification in the process of forming intimate relationships.
Keywords: Interpersonal relations; Medosebni odnosi; Partnership; Partnerstvo; Svetovni splet; World Wide Web; Slovenia; Slovenija; heteroseksualci; homoseksualci